DYNAMIC VISUALIZATION OF EDUCATIONAL MATERIAL USING THE TIMELINEJS MULTIMEDIA TOOL - Bondarenko, Тетяна (Journal of Information Technologies in Education (ITE), 2023)
The article discusses the features of using the Timeline.JS multimedia tool for visualizing educational material. The influence of information and communication technologies on the education sector leads to the fact that the visual way of presenting information becomes more popular and in demand, as a result of which there is a need to look for interactive approaches to the effective transfer of knowledge, skills and experience to consumers of educational services. Attention is focused on the possibilities of using the timeline as a new tool for presenting different types of content. In the course of the study, the main areas of use of timelines were analyzed: in the media, in the field of art, and in education. Active software tools for creating timelines were identified, which include: Timeline.JS, Timetoast, Рreceden, TIKI-TOKI, Timeline Maker, BEEDOCSTimeline, and as an additional tool, they are used by Canva and Prezi as part of cloud services. It is noted that Timeline.JS is software, a ready-made information product, thanks to which interactive, multimedia content is presented. An attempt was made to research the timeline as a "product" for use in the following categories: "Historical and Social Sciences", "Literary Analysis", "Science and Technology", "Biographies and Personalities", "Geography", "Natural Sciences", "Culture" , "Social changes and reforms". The rules for developing an effective timeline that can be used by educators as part of work on dynamic visualization of educational material are proposed.